Performance Improvement Strategy Sustainable Domestic Wastewater Treatment Installation (Case Study: Sanimas Neglasari Village, Sayati Village and Cipaku Village, Bandung Regency) - Imtiyaz Olaf Jatmy; Katharina Oginawati (Budapest International Research and Critics University, 2022)
The West Java Provincial Government has inaugurated a community-based sanitation program in 18 Bandung districts. Especially in the Citarum river basin, domestic waste contributes 68% to river pollution and has a water quality status for the last 10 years, showing 54% heavily polluted, 23% moderately polluted, 20% lightly polluted and only 3% meet the quality standards. . Efforts to improve the control of domestic wastewater pollution require the selection of technology which is influenced by many factors, so a theoretical and practical approach is needed that pays attention to the sustainability aspect. Neglasari Village, Banjaran Sub-district, Sayati Village, Margahayu Sub-district and Cipaku Village, Paseh Sub-district, are sub-districts in Bandung Regency that have implemented the Sanimas program that has not met the muku standard so that it is necessary to improve the performance of a sustainable Sanimas wastewater treatment plant. Of the three locations of the Sanimas wastewater treatment plant spread from upstream of the river, the location of the Sanimas wastewater treatment plant is in a densely populated area and an area prone to sanitation, also has a need for handling sanitation problems. This research was conducted using the SWOT method. SWOT analysis is carried out to obtain priority strategy recommendations.